Hydraulic fracturing method for strengthening soil foundations under building foundations during horizontal drilling - Ya. А. Pronozin; I. V. Sugonyaev; E. P. Bragar; M. D. Kaigorodov (Архитектура, строительство, транспорт)
The study analyzed the methods of hydraulic fracturing in horizontally oriented wells, along with techniques for strengthening soil foundations under existing building foundations using high-pressure injection (including those performed using sleeve grouting technology). The behavior of hydraulic fracturing in the soil mass was considered, which, in turn, also depends on the hydraulic fracturing pressure and the stress-strain state of the soil. A summary table was presented with formulas from domestic and foreign scientists for determining the pressure at which soil fracturing occurs. Based on the identified advantages and disadvantages of the considered soil foundation reinforcement methods, the authors proposed an alternative approach: strengthening the foundations using cementation during horizontally oriented excavation. The essence of the technology lies in the installation (using technologies that allow for trenchless horizontal drilling) of horizontal polyethylene (coiled tubing) pipes under or along the building foundation. Through these pipes, using sleeve grouting technology, a hardening solution will be injected into the soil under pressure equal to the soil fracturing pressure. This will create hydraulic fractures in the soil, thereby increasing its mechanical characteristics.